MR-TADF blue light material and application thereof in near-infrared exciplex OLED

By designing large sterically hindered organic blue light luminescent materials with dual characteristics of MR and TADF, the problems of insufficient luminescence efficiency and chemical structure diversity of near-infrared excitation composites are solved, and the near-infrared luminescence of high-efficiency and narrow spectral bands are achieved, and the performance of OLEDs of excitation composites is improved.

CN119708033AActive Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411798841.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The luminescence efficiency and chemical structural diversity of near-infrared excitation composites are far behind that of single-molecular near-infrared TADF materials.

Method used

A class of organic blue light luminescent materials with large sterically hindered large organic blue light luminescent materials with dual characteristics of multiple resonance (MR) and thermally activated delayed fluorescence (TADF) were designed. By utilizing the MR effect and TADF excited state synergy strategy, the material's high-efficiency narrow spectral band luminescence is achieved, and it is blended with classic blue light materials as an excitation composite acceptor component to prepare near-infrared excitation composite OLEDs.

Benefits of technology

It achieves a high-efficiency, narrow spectrum band near infrared luminescence, improves the luminous efficiency and color purity of excitation composite OLEDs, and has excellent carrier transmission performance and high thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708033A_ABST
    Figure CN119708033A_ABST
Patent Text Reader

Abstract

The invention discloses an MR-TADF blue light emitting material and an application of the MR-TADF blue light emitting material in a near-infrared exciplex organic light emitting device (OLED). The blue light emitting material with the MR-TADF characteristic is obtained through a Suzuki coupling reaction of a 1-quinolinacridine diketone unit and a 7-dioxaboronaphtho anthracene unit, and the blue light emitting material with the MR-TADF characteristic is obtained. According to the near-infrared near-infrared exciplex luminescent material, the near-infrared near-infrared exciplex luminescent material is taken as an acceptor component of an exciplex, an m-MTDATA blue fluorescent material is taken as a donor component of the exciplex, the near-infrared near-infrared exciplex luminescent material and the m-MTDATA blue fluorescent material are mixed according to different proportions through a solution method to prepare an active luminescent layer, and efficient near-infrared exciplex luminescence can be realized. Research results show that OLEDs processed by a solution of the compound highlight the advantage of high near-infrared luminous efficiency, the electroluminescent peak of the device is located in the range of 706-726 nm, the corresponding maximum external quantum efficiency (EQE) is in the range of 0.35-0.17%, and the compound has attractive application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of luminescence, display lighting and biomedical technology, and specifically relates to a type of double MR units comprising a nitrogen carbonyl core with multi-resonance (MR) characteristics and a boron oxygen core with MR characteristics, thereby obtaining an organic multi-resonance thermally activated delayed fluorescence (MR-TADF) blue light material, and using the material as an acceptor component of an exciplex to prepare near-infrared exciplex organic electroluminescent devices (OLEDs). Background Art

[0002] Organic light-emitting diodes (OLEDs) have received extensive attention since their advent in the 20th century. Due to their unique advantages such as thinness, transparency, and bendability, they have been used in lighting, screen display, and other fields. Among them, near-infrared organic light-emitting diodes (NIR-OLEDs) have broad application prospects in luminescence, display lighting, and biomedicine. The introduction of thermally activated delayed fluorescence (TADF) materials in 2012 greatly accelerated the development of OLEDs (Nature, 2012, 492, 234). However, TADF materials still have problems such as high turn-on voltage, large efficiency roll-off at high brightness, and complex molecular synthesis. The exciplex consists of two parts, the donor and the acceptor. Its highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are located on the donor molecule and the acceptor molecule, respectively, so that the exciplex has a smaller △EST and achieves 100% exciton utilization through the reverse gap crossing process (RISC). Compared with electroluminescent devices constructed with pure organic TADF light-emitting layer materials, electroluminescent devices based on exciplex luminescent active layers have the advantages of lower turn-on voltage and reduced efficiency roll-off at high brightness. In particular, exciplexes only need to blend two simple donor and acceptor materials to obtain new materials with relatively red-shifted emission. In 2016, Monkman blended OZDBPHZ and m-MTDATA to obtain a near-infrared exciplex for the first time, proving the great potential of deep red / near-infrared exciplex emitters in OLED applications (Angew. Chem. Int. Ed. 2016, 55, 5739-5744). In 2020, Liao Liangsheng's research group blended a green light material with a wavelength of 510 nm and TCTA to obtain a near-infrared exciplex emitting at 730 nm, with an efficiency of only 0.09%. In 2021, based on this material, it was derived and combined with PO-01 to obtain a near-infrared exciplex emitting at 750 nm, with an efficiency of 0.23%. Summary of the invention

[0003] There are few reports on near-infrared exciplexes, and their luminescence efficiency and chemical structure diversity lag far behind those of single-molecule near-infrared TADF materials.

[0004] The present invention couples a double MR unit containing a nitrogen carbonyl core with multiple resonance (MR) characteristics and a boron oxygen core with MR characteristics, and designs a class of organic blue light-emitting materials with dual MR and TADF characteristics and large steric hindrance. 1) The MR effect and TADF excited state synergistic strategy are used to achieve high-efficiency narrow-spectrum luminescence of the material; 2) The large space brought by the large torsion of the two units and the steric hindrance of the tert-butyl group are used to inhibit aggregate luminescence; 3) It is selected as the exciplex acceptor component, and combined with the classic blue light material 4,4',4''-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA) as the donor component, a near-infrared exciplex OLED with strong anti-heavy doping ability and high luminescence efficiency is obtained, which is of great significance for enriching the near-infrared exciplex system.

[0005] One of the purposes of the present invention is to provide a type of MR-TADF blue light emitting material, wherein a type of blue light emitting material having MR-TADF characteristics is obtained by Suzuki coupling reaction of 1-quinoline acridine dione unit and 7-dioxaboronaphthalene anthracene unit. The MR-TADF blue light emitting material has the structural feature shown in formula (1):

[0006] Formula (1).

[0007] Wherein: the R group is hydrogen or tert-butyl.

[0008] Specifically, the representative compound structure of the MR-TADF blue light emitting material provided by the present invention is as follows: .

[0009] Another object of the present invention is to provide the use of such organic MR-TADF blue light emitting materials in the preparation of organic electroluminescent devices (OLEDs).

[0010] The structure of the electroluminescent device is as follows: from bottom to top, there are substrate, anode electrode, hole injection layer, active luminescent layer, electron transport layer, electron injection layer and cathode electrode. The active luminescent layer is prepared by mixing 4,4',4''-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA) as the donor component of the luminescent active layer and the MR-TADF blue light material provided by the present invention as the acceptor component by solution method in different proportions; or, the active luminescent layer is prepared by mixing the MR-TADF blue light material provided by the present invention as the acceptor component of the luminescent layer and the classic blue light material m-MTDATA as the donor component by solution method in different proportions.

[0011] Among them, indium tin oxide (ITO) glass is the substrate and anode material, PEDOT:PSS is the hole injection layer material, TmPyPB is the electron transport layer material, LiF is the electron injection layer material, and metal aluminum (Al) is the cathode material.

[0012] In an exemplary embodiment of the present invention, a near-infrared exciplex organic electroluminescent device is provided, and its structure is: ITO (110 nm) / PEDOT:PSS (40 nm) / Exciplex (40 nm) / TmPyPb (55 nm) / LiF (1 nm) / Al (150 nm). Among them, Exciplex is a light-emitting layer in which LY-JP and 4,4',4''-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA) are mixed in different proportions. The invention uses it as an acceptor component of a near-infrared exciplex luminescent layer material and is used in a solution-processed organic electroluminescent diode to improve the luminescent color purity, luminous efficiency and service life of the device.

[0013] Preferably, the present invention provides a MR-TADF blue light emitting material as a light emitting layer acceptor component material for use in preparing a light emitting layer of a near-infrared exciplex OLED device, and its structural formula is LY-JP: .

[0014] Preferably, the doping amount of LY-JP in the exciplex prepared by blending the organic MR-TADF blue light emitting material compound LY-JP with the donor material m-MTDATA is 10-80%, more preferably 10%-50%, further preferably 10-40%, and most preferably 20%.

[0015] In an exemplary specific embodiment of the present invention, the exciplex OLEDs prepared with the organic MR-TADF blue light emitting material compound LY-JP and the donor material m-MTDATA in a mass blending ratio of 2:8 obtained near-infrared exciplex OLEDs with near-infrared emission of 709 nm and a maximum external quantum efficiency of 0.35%.

[0016] Compared with the prior art, the present invention has at least one of the following beneficial effects: (1) The organic MR-TADF blue light emitting material of the present invention has a simple molecular structure and many modifiable sites, which can enrich the library of organic MR-TADF blue light emitting materials.

[0017] (2) The organic MR-TADF blue light emitting material of the present invention has the dual characteristics of MR effect and TADF excited state. As a near-infrared exciplex acceptor material, it has high luminescence efficiency and creates conditions for efficient exciplex near-infrared OLEDs.

[0018] (3) The organic MR-TADF blue light emitting material of the present invention has high thermal stability, good film forming performance, and excellent carrier transport performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a thermogravimetric curve of the compound LY-JP prepared in Example 1 of the present invention in a film.

[0020] Figure 2 This is the ultraviolet-visible light absorption spectrum of the compound LY-JP prepared in Example 1 of the present invention in the film.

[0021] Figure 3 This is a photoluminescence spectrum of the compound LY-JP prepared in Example 1 of the present invention in a thin film.

[0022] Figure 4 This is a graph of the delayed lifetime of the compound LY-JP prepared in Example 1 of the present invention in a 2% doped CBP film measured under a nitrogen atmosphere.

[0023] Figure 5 This is a graph showing the instantaneous lifespan of the active layer system in the film, in which the compound LY-JP prepared in Example 1 of the present invention and m-MTDATA are blended in a mass ratio of 2:8.

[0024] Figure 6 This is a delayed life curve of the active layer system in the film of the compound LY-JP prepared in Example 1 of the present invention and m-MTDATA blended in a mass ratio of 2:8.

[0025] Figure 7 This is a device structure diagram of an electroluminescent device using the compound LY-JP and m-MTDATA prepared in Example 1 of the present invention as the active light-emitting layer of the excimer complex.

[0026] Figure 8 The electroluminescence spectra of the compounds LY-JP and m-MTDATA prepared in Example 1 of the present invention at different mass blending ratios are shown.

[0027] Fig. 9 The external quantum efficiency curve of the compound LY-JP and m-MTDATA prepared in Example 1 of the present invention at different mass blending ratios is shown. DETAILED DESCRIPTION

[0028] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be understood by those skilled in the art that the specific contents described below are illustrative rather than restrictive, and the protection scope of the present invention cannot be limited thereby.

[0029] In the present invention, the preparation methods are conventional methods unless otherwise specified, and the raw materials used can be obtained from public commercial channels unless otherwise specified. Example 1

[0030] Preparation of representative compound LY-JP The specific synthetic route of the compound LY-JP of the present invention is as follows:

[0031] Synthesis route of compound LY-JP Compound M 1 Synthesis Under nitrogen atmosphere, 2,5-dibromo-1.3-difluorobenzene (30 g, 110.34 mmol), 4-tert-butylphenol (33.15 g, 220.68 mmol), potassium carbonate (K2CO3, 45.75 g, 331.02 mmol), and dry N-methylpyrrolidone (NMP, 100.0 mL) were added to a 250 mL single-necked flask, and the temperature was raised to 200 °C and stirred to react overnight. The reaction was stopped, cooled to room temperature, and the reaction solution was poured into 100 mL of distilled water for suction filtration. The filter cake was washed with 20 mL of methanol solution and vacuum dried at 60 °C to obtain a white solid M 1 : 55.12 g, yield: 93.84%. 1H NMR (400 MHz, CDCl3) δ 8.03 (dd, J =3.5, 1.7 Hz, 4H), 7.95 (s, 2H), 7.77 (d, J = 1.7 Hz, 2H), 7.50 (dd, J = 8.6,1.9 Hz, 2H), 7.40 (d, J = 8.5 Hz, 2H), 1.44 (d, J = 4.7 Hz, 36H). MALDI-TOFMS (mass m / z): 532.04 (100.0%), 530.05 (51.4%), 534.04 (48.6%), 533.05(28.6%), 531.05 (14.7%), 535.04 (13.7%), 534.05 (4.3%), 532.05 (2.2%), 536.05(2.1%).

[0032] Compound M 2 Synthesis Under nitrogen atmosphere, a 500 mL two-necked flask was charged with M 1 (30 g, 56.36 mmol), toluene (Tol, 200 mL) were precooled at low temperature for 30 min, and n-BuLi (2.4 mol / L, 72.26 mmol, 30 mL) was slowly added dropwise, and the reaction was carried out at low temperature for 1 h, and then the reaction was moved to room temperature for 2 h; precooled at low temperature for 30 min, and boron tribromide (BBr3, 90.17 mmol, 8.6 mL) was slowly added dropwise, and the reaction was carried out at low temperature for 1 h, and then the reaction was moved to room temperature for 3 h; precooled at low temperature for 10 min, and N,N-diisopropylethylamine (DIPEA, 140.89mmol, 25 mL) was slowly added dropwise, and the reaction was carried out at low temperature for 10 min, and then the reaction was moved to room temperature for 2 h; the temperature was raised to 120 °C, and the reaction was refluxed for 24 h. The reaction was stopped, cooled to room temperature, poured into 300 mL of methanol, filtered, and dried in vacuum at 60 °C to obtain a white solid M 2 : 16.5 g, yield 63.48 %. 1H NMR (400 MHz, CDCl3) δ 8.72 (d, J = 2.5 Hz, 2H), 8.72 (d, J = 2.5Hz, 2H), 7.79 (dd, J = 8.8, 2.5 Hz, 2H), 7.79 (dd, J = 8.8, 2.5 Hz, 2H), 7.47(d, J = 8.8 Hz, 2H), 7.47 (d, J = 8.8 Hz, 2H), 7.36 (s, 2H), 7.36 (s, 2H),7.26 (s, 1H), 1.56 (s, 2H), 1.48 (s, 18H), 1.48 (s, 18H), 0.07 (s, 3H).MALDI-TOF MS (mass m / z): 460.12 (100.0%), 462.12 (97.3%), 461.12 (52.3%), 463.12 (27.4%), 459.12 (24.8%), 462.13 (11.3%), 460.13 (7.1%), 464.13 (3.9%), 463.13 (1.8%), 461.13 (1.4%).

[0033] Compound M 3 Synthesis Under nitrogen atmosphere, a 250 mL single-necked flask was charged with M 2(10 g, 21.68 mmol), 4,4,4',4',5,5,5',5'-octamethyl-2,2'-bi(1,3,2-dioxaborane) (6.61 g, 26.02 mmol), potassium acetate (ACOK, 10.64 g, 108.41 mmol), [1,1'-bis(diphenylphosphino)ferrocene]dichloropalladium(II) (Pd(dppf)Cl2, 0.476 g, 0.65 mmol), dry dioxane (Diox, 120 mL), heated to 110 °C and refluxed for 24 h. Stop the reaction, cool to room temperature, extract with DCM three times (20 mL×3), combine the organic phases, and wash with water three times (30 mL*3). The organic phase was separated, dried with magnesium sulfate, filtered to remove magnesium sulfate, and DCM was removed under reduced pressure. Column chromatography was performed with PE:DCM=3:1 as the developing solvent, and the mixture was dried under vacuum at 60°C to obtain a white solid M 3 : 10.5g, yield: 95.28%. 1H NMR (400 MHz, CDCl3) δ 8.75(d, J = 2.4 Hz, 2H), 7.79 (d, J = 2.5 Hz, 1H), 7.77 (d, J = 2.5 Hz, 1H), 7.65(s, 2H), 7.50 (s, 1H), 7.48 (s, 1H), 1.48 (s, 18H), 1.40 (s, 12H). MALDI-TOFMS (mass m / z): 508.30 (100.0%), 507.30 (42.4%), 509.30 (30.4%), 510.30(5.7%), 506.30 (5.3%), 509.31 (2.6%), 507.31 (1.9%).

[0034] Compound M 4 Synthesis Under nitrogen atmosphere, methyl 2-methylbenzoate (10 g, 38.2 mmol), 2-bromoaniline (2.6 g, 15.3 mmol), potassium carbonate (5.3 g, 38.2 mmol), copper powder (244 mg, 3.82 mmol), cuprous iodide (291.4 mg, 1.53 mmol), and dry o-dichlorobenzene were added to a 250 mL single-necked flask, and the temperature was raised to 180°C for 2 days. After cooling to room temperature, O-DCB was removed by vacuum distillation, and the mixture was extracted with dichloromethane (3×30 mL). The collected organic phase was washed with water, dried, and vacuum distilled to remove the solvent, and the residue was separated by column chromatography using petroleum ether / dichloromethane (1 / 1) as the eluent to obtain a white solid M 4: 3.36 g, yield 50%. 1H NMR (400 MHz, CDCl3) δ 7.69-7.63 (m, 1H), 7.60 (d, J =1.6 Hz, 2H), 7.42-7.30 (m, 2H), 7.25-7.19 (m, 1H), 7.17-7.11 (m, 1H), 7.07(ddd, J = 8.4, 5.7, 1.8 Hz, 2H), 7.02-6.96 (m, 2H), 6.91 (d, J = 7.9 Hz, 1H), 3.41 (d, J = 7.1 Hz, 6H). MALDI-MS (m / z): calcd. 440.29 found. 439.04. MALDI-TOF MS (mass m / z): 439.04 (100.0%), 441.04 (97.4%), 440.05 (24.2%), 442.04(23.7%), 441.05 (3.6%), 443.05 (2.7%).

[0035] Compound M 5 Synthesis Under nitrogen atmosphere, a 250 mL single-necked flask was charged with M 4 (3.15 g, 7.15 mmol), sodium hydroxide (5.7 g, 143.08 mmol), ethanol 50 mL, distilled water 50 mL, heated to 100 °C and reacted for 48 h. Stop the reaction, cool to room temperature, first remove ethanol by vacuum distillation, then add hydrochloric acid to precipitate the solid and filter to obtain a white solid M 5 : 2.9 g, yield: 95%, directly added to the next step without further purification.

[0036] Compound M 6 Synthesis First, M 5 (500 mg, 1.21 mmol), oxalyl chloride (369.36 mg, 2.91 mmol), 30 ml of dry dichloromethane were placed in a 50 mL two-necked flask, two drops of dry DMF catalyst were added to the reaction system, refluxed at 55 °C for 0.5 h, and then tin tetrachloride (0.34 mL, 2.91 mmol) was injected into the reaction system and refluxed for 3 h. Cooled to room temperature, extracted (3×20 mL), washed with water, dried, and the residue was collected and column chromatography was performed using petroleum ether / dichloromethane (2 / 1) as the eluent to obtain a yellow solid M 6: 91 mg, yield 20%. 1H NMR (400 MHz, CDCl3) δ 8.69 (dd, J = 7.6, 1.6 Hz, 1H), 8.61 (dd, J = 7.7, 1.6 Hz, 1H), 8.48 (dd, J = 7.8, 1.5 Hz, 1H), 8.38 (dd, J = 7.9,1.5 Hz, 1H), 7.96 (dd, J = 7.8, 1.5 Hz, 1H), 7.68-7.59 (m, 2H), 7.46 (dd, J =8.7, 1.6 Hz, 1H), 7.42 (d, J = 7.8 Hz, 2H). MALDI-MS (m / z): calcd. 376.21found. 376.3. MALDI-TOF MS (mass m / z): 374.99 (100.0%), 376.99 (97.8%), 375.99 (22.1%), 377.99 (21.2%), 378.99 (2.6%), 377.00 (2.3%).

[0037] Synthesis of compound LY-JP Under nitrogen atmosphere, M 6(2 g, 5.3 mmol), M3 (3.24 g, 6.4 mmol), tetrakis(triphenylphosphine palladium) (122.9 mg, 0.02 mmol), potassium carbonate (2.9 g, 2.13 mmol), tetrahydrofuran 30 mL, heated to 80 ° C, reacted for 24 h. Stop the reaction, cool to room temperature, remove THF under reduced pressure distillation, extract with dichloromethane (3×30 mL), collect the organic phase by washing with water, drying, and removing the solvent by reduced pressure distillation, the residue is separated by column chromatography with petroleum ether / dichloromethane (2 / 1) as eluent to obtain yellow solid LY-JP: 1.61 g, yield: 45%. 1H NMR (400 MHz, DMSO) δ 8.62 (dd, J = 7.5, 3.1 Hz, 2H), 8.54 (s, 2H), 8.44 (d, J = 7.7 Hz, 1H), 8.05 (d, J = 7.4 Hz, 1H), 7.77 (dd, J = 16.3, 8.4 Hz, 5H), 7.58 (d, J =29.3 Hz, 2H), 7.34 (d, J = 8.4 Hz, 2H), 7.10 (t, J = 7.7 Hz, 1H), 6.82 (t, J= 7.5 Hz, 1H), 6.50 (s, 1H), 1.42 (s, 18H). MALDI-TOF MS (mass m / z): 677.27(100.0%), 678.28 (53.5%), 676.28 (24.8%), 679.28 (13.3%), 677.28 (12.5%),680.28 (2.4%). Example 2

[0038] The compound LY-JP in Example 1 was heated in the range of 30-700 °C under N 2 The temperature was raised at a rate of 20 ℃ / min under protection, and the thermogravimetric curve was measured. Figure 1 It was found that the 5% decomposition temperature of the compounds LY-JP was 392.0°C. Example 3

[0039] The compound LY-JP in Example 1 was dissolved in a toluene solution to prepare a 10 mg / mL toluene solution, which was spin-coated on the ITO surface at a speed of 1000 r / min, and the UV-visible absorption spectrum was tested at room temperature. Figure 2It can be seen that the absorption peak before 400 nm is attributed to the n-π* transition absorption of the molecule, the absorption peak around 400 nm is mainly attributed to the π-π* transition absorption of the molecule, and the absorption peak around 450 nm is a characteristic absorption peak caused by MR. Example 4

[0040] The compound LY-JP in Example 1 was dissolved in a toluene solution to prepare a 10 mg / mL toluene solution, which was spin-coated on the ITO surface at a speed of 1000 r / min, and the photoluminescence spectrum was tested at room temperature. Figure 3 It can be seen that the emission peak of LY-JP is located at 465 nm, which is a blue light emitting material; its half-peak width is less than 70 nm and is 30 nm, which is a typical characteristic of MR-TADF luminescent materials. Example 5

[0041] The fluorescence lifetime of the compound LY-JP in Example 1 in a 2% doped CBP film was tested under a nitrogen atmosphere. Figure 4 As shown, the delayed lifetime of compound LY-JP was found to be 40.15 μs after fitting, which further determined that the compound was MR-TADF material. Example 6

[0042] The compound LY-JP in Example 1 was used as the acceptor component, and the classic m-MTDATA was used as the donor component. LY-JP:m-MTDATA was mixed in a mass ratio of 2:8, and a thin film was obtained by spin coating on the ITO surface. Its instantaneous life was tested by FlS1000. Figure 5 It can be seen that after fitting, its instantaneous lifetime is 4.84 ns, indicating that the active layer of LY-JP: m-MTDATA (2:8) blend has TADF characteristics. Example 7

[0043] The compound LY-JP in Example 1 was used as the acceptor component, and the classic m-MTDATA was used as the donor component. LY-JP:m-MTDATA was mixed in a mass ratio of 2:8, and a thin film was obtained by spin coating on the ITO surface. Its instantaneous life was tested by FlS1000. Figure 6 It can be seen that after fitting, its delayed lifetime is 1.1 μs, indicating that the active layer of LY-JP: m-MTDATA (2:8) blend has TADF characteristics. Example 8

[0044] The application of the compound LY-JP in Example 1 in an organic electroluminescent device. The compound LY-JP is used as an acceptor component, the classic m-MTDATA is used as a donor component, and LY-JP:m-MTDATA is blended in a mass ratio of 2:8 as a light-emitting layer material to prepare an exciplex near-infrared device with a structure of ITO (110 nm) / PEDOT:PSS (40 nm) / Exciplex (40 nm) / TmPyPb (55 nm) / LiF (1 nm) / Al (150 nm), such as Figure 7 shown.

[0045] Among them, indium tin oxide (ITO) glass is the anode material, PEDOT:PSS is the hole injection layer material, Exciplex is the light-emitting layer mixed with LY-JP and m-MTDATA, TmPyPB is the electron transport layer material, LiF is the electron injection layer material, and metal aluminum (Al) is the cathode material. Example 9

[0046] The compound LY-JP in Example 1 was used as the active layer acceptor component, the purchased compound m-MTDATA was used as the donor component, and the mass ratio of LY-JP / m-MTDATA was 1:9; 2:8; 4:6; 5:5; 6:4; 8:2 respectively as the active light-emitting layer of the exciplex. The near-infrared electroluminescence spectrum of the exciplex obtained was as follows: Figure 8 As shown. Figure 8 It can be seen that the electroluminescence wavelengths of different doping ratios are 701 nm, 709 nm, 712 nm, 718 nm, 720 nm and 720 nm, respectively, indicating that the exciplexes formed by LY-JP and m-MTDATA at different ratios all reach near-infrared emission. Example 10

[0047] The compound LY-JP in Example 1 was used as the active layer acceptor component, the purchased compound m-MTDATA was used as the donor component, and the mass ratio of LY-JP / m-MTDATA was 1:9; 2:8; 4:6; 5:5; 6:4; 8:2 respectively as the active light-emitting layer of the exciplex. The near-infrared external quantum efficiency curve of the exciplex obtained is shown in Fig. 9 As shown. Fig. 9 It can be seen that the external quantum efficiencies of the devices with different doping ratios are 0.27%, 0.35%, 0.28%, 0.23%, 0.19% and 0.17% respectively. The electroluminescent performance parameters of the devices with different doping ratios in this embodiment are recorded in Table 1.

[0048] Table 1 Electroluminescent performance parameters of devices with different doping ratios in the embodiments of the present invention .

[0049] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A type of MR-TADF blue light emitting material, characterized in that: The chemical structure is shown in formula (1): , Formula 1 Wherein, the R group is hydrogen or tert-butyl.

2. Use of the MR-TADF blue light emitting material described in claim 1 in preparing an active light emitting layer of an organic electroluminescent device.

3. The use according to claim 2, characterized in that: The active light-emitting layer is a film made by mixing the main material and the MR-TADF blue light material described in claim 1.

4. The use according to claim 2, characterized in that: The active luminescent layer is an exciplex film prepared by mixing the MR-TADF blue light material described in claim 1 as an exciplex acceptor component with a donor component.

5. The use according to claim 4, characterized in that: The MR-TADF blue light material is a compound LY-JP of the exciplex receptor component, and its structural formula is shown below: 。 6. The use according to claim 5, characterized in that: The donor component is 4,4',4''-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), and its molecular structure is shown below: 。 7. The use according to claim 6, characterized in that: In the exciplex, the doping amount of LY-JP is 10-80%.

8. The use according to claim 7, characterized in that: In the exciplex, the doping amount of LY-JP is 10-50%.

9. The use according to claim 2, characterized in that: The structure of the electroluminescent device includes from bottom to top: a substrate, an anode electrode, a hole injection layer, an active light-emitting layer, an electron transport layer, an electron injection layer and a cathode electrode; the substrate and the anode material are indium tin oxide glass, the hole injection layer material is PEDOT:PSS, the electron transport layer material is TmPyPB, the electron injection layer material is LiF, and the cathode material is aluminum.

10. The use according to claim 6, characterized in that: The prepared organic electroluminescent device is a near-infrared excimer complex luminescent device.

Citation Information

Patent Citations

  • Organic electroluminescent device

    CN114203936A

  • Thermal activation delayed fluorescence material and electroluminescent device

    CN114957306A

  • Space charge transfer thermal activation delayed fluorescence material as well as preparation method and application thereof

    CN117924336A